Question #b6ffe
2 Answers
Jul 28, 2017
Two ways
Explanation:
We observe that these are the first few terms of a geometric sequence because the ratio of each term to the term before it is the same value ... -3.
For this sum,
the first term is
The common ratio is
Since
By the formula for summation
For this particular sum, we have
Add these up to get
Jul 28, 2017
Explanation:
"the sum to n terms of a geometric series is"
•color(white)(x)S_n=(a(1-r^n))/(1-r)
"where a is the first term, r the common ratio and n the"
"number of terms"
"here " a=1, r=(-3)/1=9/(-3)=-3 ,n=6
rArrS_6=(1(1-(-3)^6))/(1-(-3)
color(white)(rArrS_6)=(1-729)/4=-182